Mother's Behavior Attachment Model in Care for Stunting Prevention in Bangkalan District - Ulva Noviana; Heni Ekawati; Mufarika; M. Hasinuddin; Mustofa Haris (Journal Of Nursing Practice, 2023)
Background: Stunting is a state of malnutrition associated with past nutritional insufficiency so that it is included in a chronic nutritional problem. Based on data from a study on nutritional status in Indonesia in 2021, the prevalence of stunting in Bangkalan Regency is the highest among other districts in East Java, namely 38.9%, while the incidence of stunting in Indonesia is 24% (SSGI, 2021). This shows that there are high cases of stunting among toddlers in East Java, especially in Bangkalan.Purpose: This study aims to develop a model of attachment behavior for mothers in stunting prevention care in Bangkalan Regency.Methods: The research design used was analytic observational with a cross-sectional approach. The sample size is 190 mothers who have stunted children. Technical sampling using multistage random sampling and proportionate stratified random sampling technique. Latent variables (Variable X) in this study were attitude, personal agency, knowledge, maternal parenting intentions, environmental barriers, and habits, and the dependent variable (Y) in this study was the mother's attachment behavior with 19 observed variables or indicators. The analysis technique used is SEM-PLS. Results: The latent variables that have significance for the attachment behavior of mothers in stunting prevention care are knowledge and intentions. The attitude variable directly and significantly influences the mother's attitude in forming intentions that lead to attachment behavior of the mother in caring for stunting prevention in children under two years old. Mothers who have high intentions to care for their children will be followed by concrete actions in the form of attachment behavior in the form of stunting prevention care. Mothers who have good knowledge about how to prevent stunting, the causes of stunting, and the short-term or long-term effects of stunting will move the mother and attach the mother to her baby. Attitude is one of the factors that influence the formation of a mother's intention in the behavior of a mother's caring attachment to her child.Conclusion: Knowledge and intention variables shape mother's attachment behavior in stunting prevention care. Mother's attitude influences the mother's intention in attachment behavior in stunting prevention care.